A study on drought assessment in the Yi Luo River Basin based on SWAT - Xianqi Zhang; Peng Chen; Shengnan Dai (Ecological Indicators)
This study delves into the hydrological cycle and drought characteristics of the Yi-Luo River Basin. By quantitatively assessing the impact of climate change on historical runoff variations in the basin, it provides a scientific basis for the rational planning of water and soil resources and the formulation of drought response strategies in the Yi-Luo River Basin. It offers more in-depth guidance for water resource management and ecological protection in the basin. Utilizing the SWAT model, a comprehensive assessment of the drought situation in the Yi-Luo River Basin from 1983 to 2023 was conducted. The study constructed a distributed hydrological model and a drought evaluation model for the basin, combined with GIS technology, to deeply analyze hydrological processes and drought characteristics. It was found that the drought phenomenon in the Yi-Luo River Basin has distinct seasonal and cyclical characteristics, with higher drought rates in summer and autumn due to insufficient precipitation, and a cyclical trend of increasing then decreasing and then increasing again since the 20th century. The spatial distribution characteristics of drought show that extreme and severe droughts are mainly concentrated in the middle reaches of the basin, especially in the Ruyang area, while the upper mountainous areas and downstream plains are generally characterized by mild drought. The distribution characteristics of drought duration indicate that the average duration of drought in the Yi-Luo River Basin is about 32 months, with severe and extreme droughts lasting about 16 months. Drought is more persistent in the middle reaches, while the upper and lower reaches have shorter drought periods. The spatial distribution characteristics of drought intensity show that the average drought intensity in the basin is 25, with higher drought intensity in the central and eastern parts facing more severe droughts. The impact of extreme droughts is relatively small in the upper and middle reaches and the northern part of the basin.